2020
DOI: 10.3390/ijms21165625
|View full text |Cite
|
Sign up to set email alerts
|

Aromatase Inhibitors—Induced Musculoskeletal Disorders: Current Knowledge on Clinical and Molecular Aspects

Abstract: Aromatase inhibitors (AIs) have radically changed the prognosis of hormone receptor positive breast cancer (BC) in post-menopausal women, and are a mainstay of the adjuvant therapy for BC after surgery in place of, or following, Tamoxifen. However, AIs aren’t side effect-free; frequent adverse events involve the musculoskeletal system, in the form of bone loss, AI-associated arthralgia (AIA) syndrome and autoimmune rheumatic diseases. In this narrative review, we reported the main clinical features of these th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 184 publications
0
27
0
2
Order By: Relevance
“…Previous research has reported that sustained mechanical load could activate Wnt/β-catenin signaling in the development of osteoarthritis 58 . And activation of Wnt/β-catenin signaling led to apoptosis of IVD cells and increase of ECM degradation enzymes, thereby accelerating matrix degradation and promoting IVDD progression 52 , 59 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has reported that sustained mechanical load could activate Wnt/β-catenin signaling in the development of osteoarthritis 58 . And activation of Wnt/β-catenin signaling led to apoptosis of IVD cells and increase of ECM degradation enzymes, thereby accelerating matrix degradation and promoting IVDD progression 52 , 59 .…”
Section: Discussionmentioning
confidence: 99%
“…However, they are not free of adverse effects ( 43 ). AI-associated arthralgia (AIA) is characterized by symmetrical joint pain, mostly affecting hands, wrists, and knees, which might have significant impact on patients’ QOL and compliance of treatment ( 44 ). On the individual level, breast cancer could induce anxiety and depression, as patients cannot help but worry about their future.…”
Section: Discussionmentioning
confidence: 99%
“…It is utilized at a daily dose of 2.5–7.5 mg for five days, from the third day of the menstrual cycle [ 104 ]. Proponents believe that aromatase inhibitors are superior to CC, easy to use, and safe, but clinical consequences show a risk of osteoporosis, as well as adverse effects on the cardiovascular system and lipid levels [ 105 , 106 ]. Although some aromatase inhibitors may replace CC as first-line drug therapies, CC is still considered the drug of first choice for women with PCOS.…”
Section: Selective Estrogen Receptor Modulatorsmentioning
confidence: 99%